Distance learning in early childhood education in Jayapura, Papua Province - Dyan Pratiwi; Faisal Riza Hasbullah (Universitas Ahmad Dahlan, 2021)
Distance learning (PJJ) is an alternative to learning during the Covid 19 pandemic. This article aims to find out PJJ in early childhood education in Jayapura, Papua Province. The research method used is descriptive qualitative by taking data from six early childhood education institutions in Jayapura, Papua. The results of this study indicate that the form of distance learning in early childhood education in Jayapura is by submitting children's worksheets every week, using the Zoom meeting application, using the Whatsapp application, and home visits. The results obtained from this study can be used as information about distance learning in PAUD in Jayapura and can be used as an evaluation of the implementation of PJJ for the government and PAUD institutions in order to manage the education system in Indonesia more effectively, efficiently, and optimally.